Epidemiology of soil-transmitted helminth infections in Semarang, Central Java, Indonesia. - Johanna Kurscheid; Budi Laksono; M J Park; Archie C A Clements; Ross Sadler; James S McCarthy; Susana V Nery; Ricardo Soares-Magalhaes; Kate Halton; Suharyo Hadisaputro; Alice Richardson; Léa Indjein; et al. (PLoS Neglected Tropical Diseases, 2020)
Soil-transmitted helminth (STH) infections are endemic in Indonesia. However, prevalence data for many parts of the country are incomplete. The aim of this study was to determine human STH prevalence and knowledge and practices relating to STH risk behaviour, to provide a current view of the status of STH infection in rural communities in Central Java. A cross-sectional survey of 16 villages was conducted in Semarang, Central Java in 2015. Demographic and household data together with information about knowledge and practices relating to STH and hygiene were elicited through face-to-face interviews. Stool samples were collected and examined using the flotation method. Children (aged 2-12 years) also had their haemoglobin (Hb) levels, height and weight data collected, and BMI estimated. Data were analysed using univariate logistic regression analysis. A total of 6,466 individuals with a mean age of 33.5 years (range: 2-93) from 2,195 households were interviewed. The overall prevalence of STH was 33.8% with Ascaris lumbricoides (roundworm) the predominant nematode identified (prevalence = 26.0%). Hookworm and Trichuris trichiura (whipworm) were found in 7.9% and 1.8% of participants, respectively. Females were at increased odds of infection with A. lumbricoides (adjusted OR 1.14, 95% CI [1.02-1.29], p = 0.02). Adults in age groups 51-60 and over 60 years had the highest odds of being infected with hookworm (adjusted OR 3.01, 95% CI [1.84-4.91], p<0.001 and adjusted OR 3.79, 95% CI [2.30-6.26], p<0.001, respectively) compared to 6-12 year olds. Farmers also had higher odds of being infected with hookworm (adjusted OR 2.36, 95% CI [1.17-4.76], p = 0.02) compared to other occupation categories. Poverty (OR 2.14, 95% CI [1.77-2.58], p<0.001), overcrowding (OR 1.35, 95% CI [1.27-1.44], p<0.001), goat ownership (OR 1.61, 95% CI [1.10-2.41], p = 0.02) and the presence of dry floor space in the home (OR 0.73, 95% CI [0.58-0.91], p = 0.01) were all household factors significantly associated with an increased odds of infection. Infection with STH was not significantly associated with the gastrointestinal illness (p>0.05), BMI or Hb levels; however, one third of all 2-12 year olds surveyed were found to be anaemic (i.e. Hb concentrations below 110g/l or 115g/l for children under 5 and 5 years or older, respectively), with a greater proportion of school-age children at risk. Knowledge and behaviour related to hygiene and gastrointestinal diseases varied widely and were generally not associated with STH infection. The study revealed that STH infection remains endemic in Central Java despite ongoing deworming programs. Current control efforts would benefit from being re-evaluated to determine a more effective way forward.